Prevalence of trachoma in the Far North region of Cameroon: results of a survey in 27 Health Districts. - Blaise Noa Noatina; Giles Kagmeni; Marcellin Nimpa Mengouo; Henri Claude Moungui; Ann Tarini; Yaobi Zhang; Assumpta Lucienne Françoise Bella (Public Library of Science (PLoS), 2013)
BACKGROUND: Cameroon is known to be endemic with trachoma. To appreciate the burden of the disease and facilitate the national planning of trachoma control in the integrated control program for the neglected tropical diseases, an epidemiological mapping of trachoma was conducted in the Far North region in 2010-11. METHODOLOGY: A cross-sectional, cluster random sampling survey was carried out. The survey focused on two target populations: children aged 1 to 9 years for the prevalence of active trachoma and those aged 15 and over for the prevalence of trichiasis (TT). The sample frame was an exhaustive list of villages and neighborhoods of Health Districts (HDs). The World Health Organization simplified trachoma grading system was used for the recognition and registration of cases of trachoma. PRINCIPAL FINDINGS: 48,844 children aged 1 to 9 years and 41,533 people aged 15 and over were examined. In children aged 1-9 years, the overall prevalence of trachomatous inflammation-follicular (TF) was 11.2% (95% confidence intervals (CI): 11.0-11.5%). More girls were affected than boys (p = 0.003). Thirteen (13) of 27 HDs in the region showed TF prevalence of ≥10%. The overall TT prevalence was 1.0% (95% CI: 0.9-1.1%). There were estimated 17193 (95% CI: 12576-25860) TT cases in the region. The prevalence of blindness was 0.04% (95% CI: 0.03-0.07%) and visual impairment was 0.09% (95% CI: 0.07-0.13%). CONCLUSIONS/SIGNIFICANCE: The survey confirmed that trachoma is a public health problem in the Far North region with 13 HDs qualified for district-level mass drug administration with azithromycin. It provided a foundation for the national program to plan and implement the SAFE strategy in the region. Effort must be made to find resources to provide the surgical operations to the 17193 TT cases and prevent them from becoming blind.